The Creative Embodiment of the Omani Physalis Plant Through Ceramic Sculpture: An Experimental Study (Al-Academy, 2026)
This research explores the artistic embodiment of the Physalis plant, also known as ground cherry in Oman, through ceramic sculpture. It is a technical and creative study conducted by researchers using contemporary artistic techniques such as press molding, plaster mold casting, and other methods. The study aims to investigate the aesthetic and expressive values of the Physalis fruit by analyzing its organic details, which are characterized by their delicate and intricate structure.The significance of this research lies in documenting the creative practice, through which innovative approaches were explored to produce ceramic sculptures. This study addresses a research gap in ceramic sculpture inspired by natural plants and provides an important reference for artists and researchers in this field. Additionally, the research highlights the challenges artists face in recreating natural forms, such as the difficulty of controlling raw materials like clay and maintaining fine details during ceramic shaping and firing.The study adopts a Practice-Based Research (PBR) methodology, which emphasizes knowledge exploration through hands-on application. This approach generates new knowledge through creative and experimental processes, with the practitioner playing a central role in the research. The study seeks to identify the best artistic techniques for embodying the Omani Physalis by conducting multiple sculptural experiments. Researchers experimented with various techniques, such as sculpting the fruit form in ceramics and using ceramic molds, followed by an analysis of the produced works. The findings reveal that the natural characteristics of the Physalis plant—such as its transparent texture and delicate leaf structure—offer high aesthetic and expressive potential. These features can be translated into ceramic designs that reflect a balance between fragility and strength, opening new horizons in ceramic art.The study resulted in several creative solutions and aesthetic values that helped overcome technical challenges. One of the key findings is that this type of research is highly valuable, as it bridges the connection between art and nature. The study also defines the role of artists in developing new techniques that enable them to create detailed and expressive sculptural works.